FROM MASS TO COMMUNITY: SMALL GROUP STRATEGY AS MITIGATION FOR SPIRITUAL ALIENATION IN THE DIGITAL AGE - Evans Winata (CV Naskah Aceh, 2026)
The digital era presents a paradox: unprecedented connectivity coexists with profound spiritual alienation. Contemporary churches, particularly those exceeding 200 members, increasingly experience